Genome-Wide Identification of the NHX Gene Family in Punica granatum L. and Their Expressional Patterns under Salt Stress - Jianmei Dong; Cuiyu Liu; Yuying Wang; Yujie Zhao; Dapeng Ge; Zhaohe Yuan (Agronomy, 2021)
Most cultivated lands are suffering from soil salinization, which is a global problem affecting agricultural development and economy. High NaCl concentrations in the soil result in the accumulation of toxic Cl− and Na+ in plants. Na+/H+ antiporter (NHX) can regulate Na+ compartmentalization or efflux to reduce Na+ toxicity. This study aims to identify the NHX genes in pomegranate (Punica granatum L.) from the genome sequences and investigate their expression patterns under different concentrations of NaCl stress. In this study, we used the sequences of PgNHXs to analyze the physicochemical properties, phylogenetic evolution, conserved motifs, gene structures, cis-acting elements, protein tertiary structure and expression pattern. A total of 10 PgNHX genes were identified, and divided into three clades. Conserved motifs and gene structures showed that most of them had an amiloride-binding site (FFI/LY/FLLPPI), except for the members of clade III. There were multiple cis-acting elements involved in abiotic stress in PgNHX genes. Additionally, protein-protein interaction network analysis suggested that PgNHXs might play crucial roles in keeping a balance of Na+ in cells. The qRT-PCR analysis suggested that PgNHXs had tissue-specific expressional patterns under salt stress. Overall, our findings indicated that the PgNHXs could play significant roles in response to salt stress. The theoretical foundation was established in the present study for the further functional characterization of the NHX gene family in pomegranate.